MEDIA DEVELOPMENT OF MATERIAL BOOKLETS PRAYING PERSONAL POETRY FOR GRADE IV SD STUDENTS - Wulandari, Tika; Sismulyasih, Nugraheti; Sari, Elok Fariha (Universitas Negeri Semarang, 2019)
Based on pre-research in class IV SDN Tambangan 01 found a lack of innovation. So it was been an impact on the low learning outcomes. Submission of material by the teacher still seems dominant. So a researcher wants to develop a media booklet. This study aims to develop a media booklet, studies the feasibility and effectiveness of the media booklet on the material express personal poetry in class IV SDN Tambangan 01 Semarang City. The method wich had been used in this research was a Sugiyono Research and Development (R&D) which consists of (1) potential and problem stages, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trials, (7) product revisions, (8) trials usage. The subjects of this stdy were several students in class IV SDN Tambangan 01 Semarang. Data collecting techniques were using observation, interviews, documentation, questionnaires, and tests. Data analyzing techniques were using product feasibility, initial and final data analysis (t test and N-Gain test). The result of the booklet feasibility test that from media experts obtained the percentage of 93.45% and the assessment of material experts obtained the percentage 91.6%. The booklet media effectiveness used in accordance with the result of the t test showed t arithmetic> t table (11,367> 1,697), then Ho was rejected and the pretest and posttest gain a result which was 0,552 with a criteria that support the effectiveness booklet media . The result of the questionnaire responses of teachers and students showed a very positive answer that make booklet media was more effective in its users.